3D-Sensorsystem für den kollisionsfreien Betrieb flexibler Strahlentherapiegeräte - Buschhaus, Arnd; Franke, Jörg; Reitelshöfer, Sebastian; Ziegler, Christian; Röttenbacher, Maren (Internationales Forum Mechatronik 2013, 2013)
Ein bedeutendes Mittel zur Behandlung von Tumoren stellt ionisierende Strahlung dar. Neben der Verwendung einer geeigneten Strahlquelle kommt dabei vor allem der Bestrahlungsdosis zur Tumorbehandlung während der Therapieablaufs eine bedeutende Rolle zu. Ziel dieser Behandlungsmethoden ist es, die Belastung des umliegenden Gewebes zu reduzieren und die zeitliche Dauer möglichst kurz zu gestalten. Moderne Therapiegeräte ermöglichen hierzu eine Anpassung der Bestrahlungsrichtung bezüglich des Tumors. Der Strahlenaustritt am Gerät wird dabei auf einer kreisförmigen Bahn um den Tumor bewegt, der sich im Isozentrum der Bestrahlung befindet. Zur flexiblen Behandlung von Tumoren besteht zunehmend die Forderung nach einer Erhöhung der kinematischen Freiheitsgrade des bestrahlenden Gerätes. Einen wesentlichen Einfluss auf die Therapiedauer hat derzeit die notwendige geringe Geschwindigkeit der Kinematik, mit welcher diese zwischen den verschiedenen Bestrahlpositionen bewegt wird. Eine geringe Geschwindigkeit ist erforderlich, um Kollisionen des Patienten mit der Kinematik zu vermeiden und Verletzungen zu verhindern. Aus dieser Forderung ergibt sich ein ungünstiges Verhältnis von den Positionierzeiten des Gerätes zu den Bestrahlzeiten. Dies führt durch die längere Therapiedauer zu einer zusätzlichen Belastung für den Patienten und zu einer schlechteren Auslastung der investitionsintensiven Therapiegeräte. Durch eine zuverlässige Detektion und Positionsbestimmung des Patienten während der Behandlung und das Ableiten geeigneter Reaktionsstrategien ist es möglich die zulässigen Geschwindigkeiten der Therapiegerätekinematik zu erhöhen und somit die Nebenzeiten signifikant zu reduzieren. Um dies zu ermöglichen ist jedoch eine robuste Erkennung des Patienten und potentieller Kollisionen notwendig. In der Medizintechnik und auch der Strahlentherapie werden mittlerweile zunehmend 3D-Kamerasysteme verwendet, die bei der hochgenauen Patientenpositionierung oder der Atemverfolgung eingesetzt werden. Diese Kamerasysteme qualifizieren sich ebenfalls zur behandlungsbegleitenden überwachung des Patienten um Bewegungen zu erkennen. Hierzu ist jedoch eine robuste Verarbeitung der Kameradaten wesentlich. So müssen anfangs fehlerhafte Bildinformationen durch eine geeignete Filterung eliminiert werden. Eine sich anschließende Erkennung des Patienten muss im Weiteren mehreren Anforderungen genügen: So sind Patienten unterschiedlicher Physiognomie zu erkennen, die Lage des Patienten zur Kamera ist per se nicht bekannt und die Position der Patientenliege ist variabel. Die Patientenerkennung wird über einen Algorithmus realisiert, der die räumlichen Lageinformationen der 3D-Kamera verwendet und über den zusammenhängende Regionen bestimmt werden. Die dem Patienten zugewiesenen Bildpunkte werden im Anschluss binärisiert und im Nachgang die Kanten des Binärbildes bereinigt sowie isolierte Bildbereiche beseitigt. Anschließend wird aus den Bildinformationen ein Skelett des Patienten extrahiert. Diese Körperstruktur wird im Weiteren durch Gelenke erweitert, um z. B. eine Unterscheidung der Gliedmaßen zu ermöglichen und deren Winkelstellungen zu ermitteln. Unter Zuhilfenahme dieser Informationen werden im Nachgang Hüllkörper zur Beschreibung des Patienten erzeugt. Basierend auf einem Bestrahlungsplan werden bei der Behandlung die Stellungen des Therapiegeräts und der Kinematik sowie die optimalen Bahntrajektorien zwischen den Bestrahlpositionen generiert. Während der Durchführung der Bewegungsprogramme wird die aktuelle Stellung des Strahlentherapiegeräts auf Kollisionen mit dem Patienten überprüft. Diese erfolgt über eine Durchdringungsanalyse der Hüllkörperrepräsentation des Patienten und einer geometrischen Repräsentation der Kinematik und des Strahlentherapiegeräts. Die zuverlässige Erkennung des Patienten bei den üblichen Körperhaltungen durch die dargestellten Bildverarbeitungsroutinen konnte im Rahmen der Arbeiten experimentell nachgewiesen werden. Potentielle Gefahrensituationen wurden zuverlässig vom Softwaresystem erkannt und resultieren in einem Stopp der Kinematik.
Keywords: - Robotik - 3D Bildverarbeitung - Strahlentherapie - Kollisionsanalyse - Regelung; 3D-Kameras; B|Mech; Industrieroboter-Assistenzsystem; PMD-Kamera; Roboter

Accuracy Analysis and Improvement for Cooperative Industrial Robots - Buschhaus, Arnd; Wagner, Maximilian; Franke, Jörg; Reitelshöfer, Sebastian; Heß, Peter (Proceedings of the 14th International Conference on Informatics in Control, Automation and Robotics, 2017)

Automated Optimization of Complex Three-dimensional Robot Trajectories - Buschhaus, Arnd; Franke, Jörg; Reitinger, Peter (2nd IEEE International Conference on Control, Automation and Robotics, 2016)
Jointed-arm robots can be used for a broad variety of tasks. Thereby the planning of complex three-dimensional trajectories can be very time consuming. This is especially true, if a defined movement of the work-piece relative to a process-tool is required. For such tasks, the trajectory programming is greatly supported by 3D-kinematic simulation tools. However, the dynamic attributes of the real robot are unconsidered by this way of programming. Geometric discontinuities within the process path lead to abrupt changes of the Tool Center Point (TCP) orientation, which results in infinite values for acceleration and deceleration of the robot axis. Adjacent process planes, which share the same edges but have different angles of their surface normals, require an abrupt change of the work-piece orientation relative to the tool. This results in irregularities of the robot movements. To overcome this problem, a method and system for an automated trajectory optimization of complex 3D-robot movements is developed at the FAPS institute. Thereby in critical areas of the process pathway a continuous and defined pre- or post-rotation of the work-piece relative to the tool is achieved, considering process and robot specific boundary conditions. Further algorithms have been developed, which enable an automated control of the process equipment and an automatic generation of non-process relevant trajectory segments for a TCP reorientation. In addition, the velocity parameters of the robot movements are automatically modified. By this way of proceeding, a steady movement speed of the tool relative to process planes and a smoother robot movement is guaranteed, which has been as well validated by first experiments.
Keywords: B|Mech

Geometry-Based 6D-Pose Visual Servoing System Enabling Accuracy Improvements of Industrial Robots - Buschhaus, Arnd; Franke, Jörg; Grünsteudel, Holger (IEEE 2016 International Conference on Advanced Mechatronic Systems, 2016)
Keywords: B|Mech

Highly Efficient Control System Enabling Robot Accuracy Improvement - Buschhaus, Arnd; Blank, Andreas; Ziegler, Christian; Franke, Jörg (5th CATS 2014 - CIRP Conference on Assembly Technologies and Systems, 2014)
The developed control system utilizes existing network technologies and uses data of sensor systems for continuous process monitoring to derive the robots actual state in course of its movement. In case of a high speed camera the image data is acquired by the control system via a first thread and subsequently the actual robot position is calculated based on this data. At the same time, for determining the robots target state, the system continuously requests the robots nominal position from the robot controller by utilizing a parallel second thread. The information describing the robots actual state is then compared with the sensor data for calculating offset values. These offset values are subsequently filtered and a correction value is calculated. In a third parallel thread new movement instructions are generated, considering the offset values as well as the robots target trajectory. Finally, for remote control of the robot, these movement instructions are transferred to the robot controller. (C) 2014 Elsevier B.V.
Keywords: Industrial Robot; Control System; Accuracy Improvement

Industrial Robots Accuracy Optimization in the Area of Structuring and Metallization of Three Dimensional Molded Interconnect Devices - Buschhaus, Arnd; Franke, Jörg (Robotics in Smart Manufacturing, 2013)
Based on their beneficial features, there is a growing importance of three dimensional molded interconnect devices. An important process in course of their manufacturing is the metallization for generating the conducting pattern layout. Therefore, flexible handling devices like industrial robots have to be provided, moving the substrate with a high accuracy relative to a process nozzle. Due to complex three dimensional conducting patterns an offline programming of the robots trajectory is needed. Given to the real robot, this leads to a geometric precision of the movement not meeting the high product demands. To overcome this problem, the usage of modern optical sensor systems for online process monitoring and subsequent real-time robot control is investigated. By continuously supervising the conducting pattern generation the actual robots position is derived. Subsequently, compared to the robots target position, geometric correction values are determined and given to the robot control position deviations can be compensated. For this way of proceeding a highly efficient methodology for image data processing and correction value determination has to be developed. First experiments already show good results with very high geometric accuracies and a very promising data-processing performance.
Keywords: 3D-MID; B|Mech; closed-loop-control; Robotics; sensor systems

Inline calibration method for robot supported process tasks with high accuracy requirements - Buschhaus, Arnd; Wagner, Maximilian; Franke, Jörg (2017 IEEE International Conference on Advanced Intelligent Mechatronics (AIM), 2017)

Method for Vectorial Robot Movement Determination Enabling Accuracy Improvements - Buschhaus, Arnd; Franke, Jörg; Apel, Nicky (2015 IEEE International Conference on Control, Automation and Robotics, 2015)
Promising approaches for robot accuracy improvements belong to the visual servoing methods. These methods comprise closed-loop control systems, which utilize sensors to guide the robot relative to visible features of a work-piece. However, the known methods show limitations regarding their usability for highly accurate applications or tasks without a predetermined process pathway. To overcome this problem, at FAPS a system for high-speed monitoring of the work-piece's movement is investigated. The system enables a closed-loop control of the robots motion, if a deviation between actual and planned movement is determined. For the actual movement determination, a highly efficient and accurate image data processing system, based on a vectorial movement deter-mination of fiducial markers is developed. In this context, a highly efficient and geometrical accurate actual state determi-nation constitutes a significant challenge. Experiments show, that the system allows a position determination in an area of ten microns at a frequency faster than 500 Hz, thus enabling a reactive robot control and accuracy improvement.
Keywords: A. Buschhaus; B|Mech; Image processing; robot control; Visual servoing

Optimierung der Industrieroboter-Geschicklichkeit durch Zwei-Arm-Kinematik, PMD Sensorüberwachung und aufgabenorientierte Programmierung für die flexibel automatisierte Komplettmontage von Elektromotoren - Buschhaus, Arnd; Franke, Jörg; Dobroschke, Andreas (2011)
Keywords: 3D-Kameras; B|Mech; electric drive; Roboter

Planning and Control of Robot-Assisted Process Cells for Structuring and Metallization of 3D-MID - Buschhaus, Arnd; Franke, Jörg (10th International Congress Molded Interconnect Devices, 2012)
Keywords: B|Mech

Universal Fine Interpolation Algorithms for Accuracy Improvements of Industrial Robots - Buschhaus, Arnd; Franke, Jörg; Krusemark, Stefan; Karlidag, Engin (IEEE 8th International Congress on Ultra Modern Telecommunications & Control Systems, 2016)
Keywords: B|Mech

Usage of Industrial Robots as Flexible Handling Devices Supporting the Process of Three Dimensional Conductive Pattern Generation - Buschhaus, Arnd; Franke, Jörg (11th International Congress Molded Interconnect Devices, 2014)
Due to their vast number of benefits, plenty of complex and miniaturized three dimensional molded interconnect devices are developed. One especially demanding process step during their manufacturing is the geometrical exact creation of the conductive pattern layout on the different substrates' faces. Therefore, sophisticated and flexible technologies like laser direct structuring or printing processes can be used, which are subject to multiple research activities, concentrating for example on coating materials or process parameters. An additional aspect is the necessity of providing a flexible and sufficiently accurate handling device, which three dimensionally moves the substrate relative to the process nozzle applying the coating material. For this task industrial robots could be used, which inherit multiple beneficial features. One main drawback of using this type of kinematic is their relative low absolute accuracy of a few hundred microns, which is not sufficient for moving the substrate during the process with the needed accuracy. To exploit the multiple advantages which accompany the usage of standard robots, in current research activities at FAPS institute a new approach is investigated, improving their accuracy in course of complex 3D-movements. In this work, modern optical sensor systems for online process monitoring and subsequent real-time robot control are used. By continuously supervising the conducting pattern generation progress, the actual process spot position on the substrate is determined. Subsequently, this information is used to continuously derive the robots actual position. Compared with target state values, geometrical offsets between actual state and target state are calculated. Considering this information during the process, a closed-loop control of the robot control is established and the robot's movement is corrected in real-time. Thereby, position deviations are compensated and an accurate application of the conductive pattern layout on the substrate is obtained. Improving the accuracy of conventional industrial robots and as a result qualifying them for supporting the conductive pattern generation of miniaturized 3D-MID products can greatly contribute to the MID technology. With their high flexibility of movement, the advantage of design flexibility of the 3D-MID technology can be even better exploited and hence more sophisticated 3D-MID products and applications will be possible in the future.
Keywords: B|Mech; Industrial Robot; 3D-MID; Structuring; Metallization; Sensor System

Vector Based Closed-Loop Control Methodology for Industrial Robots - Buschhaus, Arnd; Blank, Andreas; Franke, Jörg (ICAR 2015 - 17th International Conference on Advanced Robotics, 2015)
Improving the absolute accuracy of industrial robots is addressed by multiple activities of research institutes and robot manufacturers. Challenging in this context is an accuracy improvement of the robot during the movement. This is due to the necessity of providing time efficient and accurate target and actual state determination modules, an adequate data synchronization and a proper correction value calculation. This information can then be used to establish an online closed-loop control of the robot. One difficulty in such a system is to guarantee a smooth and steady movement despite the continuous inaccuracy compensation. To overcome this problem, recent research activities address a vector based control method. Thereby, the path planning is transferred to an external control unit, which performs all calculation steps. Based on this calculation, movement vectors synchronized with the interpolation cycle time of the robot are computed, continuously sent to the robot controller and brought to execution. These vectors include components, which describe the deviation between actual and target state and hence allow a compensation of the inaccuracies. Thereby, the robot is "pushed" along its optimal trajectory by small increments. Experiments already show good results, allowing a reactive control together with a smooth movement execution.
Keywords: Robot; Closed-Loop Control; Absolute Accuracy Improvement; Path Planning